THE PRACTICAL IMPORTANCE OF PSYCHOLOGY IN CHILD UPBRINGING (International Conference on Medical Science, Medicine and Public Health, 2025)
A child’s personality, moral views, attitude towards work, and place in society are primarily formed within the family. Mutual respect between parents, their love and care for the child, and consistency in upbringing lay the foundation for the child’s healthy and well-rounded development. This article discusses the invaluable role of the family in raising a child. It also presents important ideas about common mistakes in family upbringing, their negative consequences, and ways to prevent them.